TRANSPARANSI DIGITAL DALAM KEUANGAN PUBLIK SYARIAH : PERAN TEKNOLOGI DALAM MENINGKATKAN EFISIENSI DAN TRANSPARANSI - Ria Nelta Febriyanti (Program Studi Ekonomi Syariah, 2024)
Digitalization has changed the way finances are managed in various sectors, including sharia-based public finance. In this context, technologies such as blockchain, big data, and sharia financial technology (fintech) provide great opportunities to improve efficiency, transparency, and financial inclusion. This article reviews the literature related to digital transformation in sharia public finance using a literature study method. The focus of the study is the application of digital technology in the management of zakat, waqf, and sharia taxes in Indonesia. The results of the study show that digitalization can accelerate the process of collecting and distributing funds, but challenges such as low digital literacy, uneven infrastructure, and regulations that do not fully support are still obstacles. Key words: Digitalization of Sharia Public Finance, Sharia Fintech, Blockchain, Big Data